Terahertz conductivity of the highly mismatched amorphous alloy, GaNBi - Vaisakh, C.P.; Foxon, C.T.; Novikov, Sergei V.; Kini, R.N. (IOP Publishing, 2017)
We report terahertz optical conductivity measurements of the highly mismatched alloy, GaNBi. We find that in these amorphous GaNBi epilayers grown using plasma assisted molecular beam epitaxy, the optical conductivity is enhanced in the samples grown at higher gallium beam equivalent pressure (BEP). The optical conductivity spectra in these pseudo-amorphous epilayers follow a Drude–Smith behaviour due to charge confinement effects. The direct current conductivity in the epilayers grown at the highest Ga BEP (3.1 × 10−7 Torr) show an increase of three orders of magnitude compared to the one grown at the lowest Ga BEP (2.0 × 10−7 Torr). Our measurements suggests a percolative transition from an insulating nature in the GaNBi epilayers grown at low Ga BEP to a highly conducting phase in the epilayers grown at high Ga BEP.